2011
DOI: 10.1080/03634523.2010.537756
|View full text |Cite
|
Sign up to set email alerts
|

Instructional Dissent in the College Classroom

Abstract: The purpose of this study was to (a) identify perceived triggering agents of student dissent in the college classroom, (b) determine common target receivers of dissent, and (c) reveal the types of dissent that students enact based on their intentional motives and construction of message content. Participants were 123 undergraduate students who completed a survey and provided multiple written narratives in response to open-ended questions. Results of a content analysis revealed that (a) common perceived trigger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
102
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(112 citation statements)
references
References 52 publications
6
102
0
4
Order By: Relevance
“…(p. 215). Goodboy (2011) found that this was the case as student narratives revealed certain teacher misbehaviors (i.e., unfair testing, unfair grading, teaching style issues, offensiveness, and indolence) were causes of student dissent responses. However, these results which were derived from qualitative data were not statistically demonstrated.…”
Section: Teacher Misbehaviorsmentioning
confidence: 90%
See 2 more Smart Citations
“…(p. 215). Goodboy (2011) found that this was the case as student narratives revealed certain teacher misbehaviors (i.e., unfair testing, unfair grading, teaching style issues, offensiveness, and indolence) were causes of student dissent responses. However, these results which were derived from qualitative data were not statistically demonstrated.…”
Section: Teacher Misbehaviorsmentioning
confidence: 90%
“…In another qualitative study, Goodboy (2011) examined the triggering agents of instructional dissent, the recipients of dissent messages, and the types of dissent communicated by college students, and reported three major conclusions. First, Goodboy found that a variety of triggering agents cause students to dissent.…”
Section: Instructional Dissentmentioning
confidence: 98%
See 1 more Smart Citation
“…It is probable that the relational dimension the Priest had established encouraged such a direct approach, along with personality dimensions of the parishioner. Indirect reactions primarily included sharing the incident, a component of dissent, an active classroom behavior (Goodboy, 2011a;Horan et al, 2010). Still, and unfortunately, some people reported leaving the Church.…”
Section: Theoretical Implications and Contributionsmentioning
confidence: 98%
“…For religious communication scholars, the application of instructional communication to a church setting provides an additional lens to understand and study this context. Importantly, as misbehaviors are linked to outcomes typically studied in organizations, such as fairness (Chory-Assad, 2002;Goodboy, 2011a;Horan, Chory, & Goodboy, 2010) and dissent (e.g., Goodboy, 2011b), further understanding misbehaviors is of value to those who study organizational communication. Carrell (2009) argued the communicative implications of religious communication, specifically: "face-to-face public speaking is an obvious central and regular task of the professional life of the clergy" (Carrell, 2009, p. 15).…”
mentioning
confidence: 99%